Social Protection: Designing Adaptive Systems to Build Resilience to Climate Change - Gilligan, Daniel O. (2022)
Daniel Gilligan GLOBAL FOOD POLICY REPORT 2022 Global Food Policy Report: Climate Change & Food Systems Global Launch Event MAY 12, 2022 - 9:30 TO 11:00AM EDT